Corn Leaf Aphids Do Not Benefit from Greenbug Feeding and Plant Damage - Barkoviak, Hayley; Enders, Laramy; Smith, Michael (My University, 2017)
Greenbugs (Schizaphis graminum) are known for their devastating effects on crops including cereal grains. Their saliva contains toxins, which break down the plants defenses and allow the aphids to utilize nitrogen from the plant. This quality makes the greenbug more destructive than other species including the corn leaf aphid (Rhopalosiphum maidis). To observe whether aphid feeding influences the success of other aphid species that later feed on the same plant, we designed an experiment which measured aphid virulence and plant damage. We found that the presence of aphids generally stunts plant growth, combined damage of two aphid species is greater than a single species, and damage done by greenbugs does not necessarily benefit corn leaf aphids.
Citation: Barkoviak, H. (2017). Corn Leaf Aphids Do Not Benefit from Greenbug Feeding and Plant Damage . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.